Dyslipidemia And Hypertension Among Indonesian Hajj Pilgrims: A Cross-Sectional Study - Ardiana, Meity; Nirwana, Wira (Jurnal Health Sains, 2024)
There has been an increase in the preval_ence of cardiovascular disease in Indonesia due to an increased preval_ence of hypertension. Cardiovascular disease is the primary cause of morbidity and mortality among Indonesian Hajj pilgrims. Dyslipidemia and hypertension are positively correlated, with dyslipidemia potentially contributing to hypertension through the mechanism of atherosclerosis. The primary objective of this study is to identify the association between hypertension and dyslipidemia among Indonesian hajj pilgrims. A cross-sectional study involving 114,069 participants in total. The Indonesian Hajj pilgrims in 2023 were the research population. Pre-embarkation medical exams were performed by qualified healthcare professionals, and data were taken from Hajj medical service records. Using bivariate analysis and the Chi-Square (χ2) test, the proportions of age and gender were compared between the hypertension and non-hypertension groups. The relationship between triglyceride, HDL, and LDL levels and hypertension was determined through logistic regression analysis. Logistic regression analysis was used to provide a multivariate analysis of the relationship between dyslipidemia and hypertension. The hypertension group has an average age of 60.2 + 11.6 years old (p<0.0001). There was no difference in the effect of gender on hypertension (p=0.105). HDL, LDL, and Triglyceride serum levels significantly affected the preval_ence of hypertension (p<0.0001). Dyslipidemia was a risk factor for hypertension with an OR of 1.084 (1.057-1.112) (95% CI). Dyslipidemia is a risk factor for hypertension. Serum levels of HDL, LDL, and triglycerides affect blood pressure.